The Expulsion by Force of the Population of the Western Ukrainian Lands in 1940th – 1950th - Сорока Ю. (Видавничо-поліграфічний центр "Київський університет", 2007)
The article deals with the problem of mass expulsions by force of the Western Ukrainianland's inhabitants in the post-war period.

Розглянуто питання масових примусових виселень жителів західноукраїнських земель у повоєнний період.
Насильницьке виселення населення західноукраїнських земель у 1940–1950-х роках